The Impact of AI Application Utilization and Innovation Learning on Academic Achievement Students in the Society 5.0 Era - Sri Yuliana; Lidia Anggraini; Fikri Al Arif (Pustaka Edukasi: Jurnal Pendidikan Indonesia, 2026)
Abstract                            The purpose of this study is to determine the effect of AI Application Utilization and Learning Innovation on Student Academic Achievement in the Society 5.0 Era. The research approach used is a quantitative approach with a population of students currently studying in Asahan Regency. The classical assumption tests used in this study were normality, heteroscedasticity, and multicollinearity tests. The regression test used in this study was multiple linear regression. The hypothesis tests used in this study were the F test, t test, and R2test. The results of this study show that simultaneously, the independent variables consisting of AI Application Utilization (X1), Learning Innovation (X2), have a positive and significant effect on the dependent variable, namely Academic Achievement (Y).   Keywords: Academic Achievement; AI Application Utilization; Learning Innovation